Implementasi Kebijakan Perlindungan Buah Lokal Bali (Studi Kasus Pada Buah Salak Bali) - David Harysusanto; A.A. Gde Putra Pemayun (Program Studi Administrasi Negara Universitas Serang Raya, 2021)
This study aims to analyze the implementation of Bali Governor Regulation number 99 of 2018 concerning the Marketing and Utilization of Balinese Local Agricultural Products, with a case study on Balinese zalacca fruit. This study used qualitative research methods. The use of descriptive qualitative research is to examine the implementation process of a public policy by describing four variable factors ranging from communication, resources, disposition and bureaucratic structure. Data were collected by conducting interviews with informants who were determined by purposive sampling technique of 9 people from business actors (supermarkets), competent government officials and zalacca farmers. Data analysis by triangulating the results of interviews, field observations and documentation. The results of the study show that the implementation process of Bali Governor Regulation Number 99, 2018 cannot implemented, with the first indicator of policy implementation regarding poor communication, with data that only 1 in 9 respondents (only 11%) received socialization from competent parties.So that it also results in resource factors, dispositions and what the author concluded were not working as well. Problems that hinder the implementation of local fruit protection of Balinese zalacca fruit are technical plant science, where the nature of fertilization and the harvest period of salak bali and barking sugar is not sustainable throughout the year.